A review : Static analysis of android malware and detection technique - Juliza, Mohamad Arif; Mohd Faizal, Ab Razak; Suryanti, Awang; Sharfah Ratibah, Tuan Mat; Nor Syahidatul Nadiah, Ismail; Ahmad Firdaus, Zainal Abidin (IEEE, 2021)
Android malware has become more widespread in recent years due to the growing popularity of Android mobile. Android malware is installed without the user’s consent on a mobile device and exhibits significant risks to users, including personal information disclosure and fraud. Furthermore, some malware may be hidden inside the mobile device using various obfuscation techniques and cause harm. To mitigate these risks, the researcher recommended a variety of detection techniques. Unfortunately, it remains challenging as Android malware continues to increase. Signature-based detection is currently used to detect malware, but unknown malware and the newest malware are not recognised in this approach. This demonstrates that developing an effective malware detection method is crucial, with an enormous gap in recent studies and methods. This study aims to present researchers with a review of Android malware detection methods and empirical findings, focusing on static analysis. The research discussed the trends of Android malware, Android vulnerabilities, static analysis approaches, and a summary of recent studies in static analysis. Additionally, future research guidelines in the static analysis are suggested to optimise the functionality of Android malware detection.